PD-L1 and IFN-γ modulate Non-Small Cell Lung Cancer (NSCLC) cell plasticity associated to immune checkpoint inhibitor (ICI)-mediated hyperprogressive disease (HPD) - Angelicola, Stefania; Giunchi, Francesca; Ruzzi, Francesca; Frascino, Mariateresa; Pitzalis, Mary; Scalambra, Laura; Semprini, Maria Sofia; Pittino, Olga Maria; Cappello, Chiara; Siracusa, Irene; Chillico, Ilaria Candida; Di Noia, Martina; et al. (Journal of translational medicine, 2025)
Background Non-Small Cell Lung Cancer (NSCLC) is the leading cause of cancer death worldwide. Although immune checkpoint inhibitors (ICIs) have shown remarkable clinical efficacy, they can also induce a paradoxical cancer acceleration, known as hyperprogressive disease (HPD), whose causative mechanisms are still unclear. Methods This study investigated the mechanisms of ICI resistance in an HPD-NSCLC model. Two primary cell cultures were established from samples of a NSCLC patient, before ICI initiation (“baseline”, NSCLC-B) and during HPD (“hyperprogression”, NSCLC-H). The cell lines were phenotypically and molecularly characterized through immunofluorescence, Western Blotting and RNA-Seq analysis. To assess cell plasticity and aggressiveness, cellular growth patterns were evaluated both in vitro and in vivo through 2D and 3D cell growth assays and patient-derived xenografts establishment. In vitro investigations, including the evaluation of cell sensitivity to interferon-gamma (IFN-γ) and cell response to PD-L1 modulation, were conducted to explore the influence of these factors on cell plasticity regulation. Results NSCLC-H exhibited increased expression of specific CD44 isoforms and a more aggressive phenotype, including organoid formation ability, compared to NSCLC-B. Plastic changes in NSCLC-H were well described by a deep transcriptome shift, that also affected IFN-γ–related genes, including PD-L1. IFN-γ–mediated cell growth inhibition was compromised in both 2D-cultured NSCLC-B and NSCLC-H cells. Further, the cytokine induced a partial activation of both type I and type II IFN-pathway mediators, together with a striking increase in NSCLC-B growth in 3D cell culture systems. Finally, low IFN-γ doses and PD-L1 modulation both promoted plastic changes in NSCLC-B, increasing CD44 expression and its ability to produce spheres. Conclusions Our findings identified plasticity as a relevant hallmark of ICI-mediated HPD by demonstrating that ICIs can modulate the IFN-γ and PD-L1 pathways, driving tumor cell plasticity and fueling HPD development.